1965
DOI: 10.1002/macp.1965.020830114
|View full text |Cite
|
Sign up to set email alerts
|

Polybenzoxazoles and polybenzothiazoles

Abstract: Polybenzoxazoles of high molecular weight were prepared easily by the solution polycondensation of 3,3'-dihydroxybenzidine dihydrochloride or 3,3'-diamino-4,4'-dihydroxybiphenyl dihydrochloride with both aromatic and aliphatic dicarboxylic acids in polyphosphoric acid. Polybenzothiazoles were prepared from 3,3'-dimercaptobenzidine dihydrochloride and dicarboxylic acids by the same procedure.Aromatic polybenzoxazoles and polybenzothiazoles showed BR excellent thermal stability up to 450 "C. in air. They were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 121 publications
(44 citation statements)
references
References 6 publications
0
40
0
Order By: Relevance
“…Polyimides (PI), polyamides (PA) and azoles (Az) were prepared by the usual polycondensation methods [22][23][24][25][26], as shown in Fig. 1.…”
Section: Preparation Of Polymersmentioning
confidence: 99%
“…Polyimides (PI), polyamides (PA) and azoles (Az) were prepared by the usual polycondensation methods [22][23][24][25][26], as shown in Fig. 1.…”
Section: Preparation Of Polymersmentioning
confidence: 99%
“…[12,[17][18][19] The second is a one-step process directly producing PBOs that includes the melt polycondensation of bis(o-aminophenol)s with aromatic dicarboxylic acid diphenyl esters, [20] and the solution polycondensation with aromatic dicarboxylic acids in acidic media like polyphosphoric acid. [3,13,21,22] The present study has two main objectives. The first is to prepare films of various aromatic PBOs through the two-step silylation method [12,[17][18][19] by the polycondensation of trimethylsilyl-substituted bis(o-aminophenol)s with aromatic dicarboxylic acid chlorides affording precursor poly(o-trimethylsiloxy-amide)s, followed by thermal cyclocondensation (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…These thermal stability data were consistent with those of the aromatic PBOs already reported in the literature. 10,11,20 In conclusion, we have found that the aminophenolnitrile route or its hydrochloride process was a simple and facile method for the synthesis of aromatic PBOs having moderately high molecular weights, as well as for that of aliphatic PBOs reported previously, compared with other known synthetic methods. In addition, the aminophenol hydrochloride-nitrile process was more useful than the parent aminophenol-nitrile route for preparing aromatic PBOs with higher molecular weights.…”
Section: Resultsmentioning
confidence: 88%
“…These IR spectra were agreed quite well with those of the aromatic PBOs reported previously. 10,11,20 The thermal stability of the aromatic PBOs 3, 4, 8, and 9 was evaluated by means of TG at a heating rate of 20°C/min in nitrogen. As expected, the two all-aromatic PBOs 3 and 8 showed the best thermal stability in terms of temperatures for 10% weight loss, which were 695 and 665°C, respectively.…”
Section: Resultsmentioning
confidence: 99%